The Mining Industry in Colonial Turkestan (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The mining industry has long been developed in the ancient regions of Turan and Turkestan. The inhabitants of this region mastered methods for identifying mineral sources and incorporating them into their daily lives. After the Russian Empire established its colonial system in Turkestan, efforts were made to locate and exploit these natural mineral resources. Significant attention was paid to discovering and utilizing coal and oil deposits, driven in large part by Russian entrepreneurs seeking high profits. This article examines the formation of the mining industry in Turkestan using primary sources.